The clinical practice patterns of fetal ultrasonography in the first-trimester: A questionnaire survey of members of the Korean Society of Ultrasound in Obstetrics and Gynecology - Kim, Kun Woo (Obstet Gynecol Sci, 2014)
OBJECTIVE: This study aimed to survey the current clinical practice of first-trimester ultrasonography among members of the Korean Society of Ultrasound in Obstetrics and Gynecology (KSUOG) and to provide basic data for making practical recommendations about first-trimester ultrasonography scan in Korea. METHODS: This survey was conducted using a self-administered anonymous questionnaire. The first-trimester in this survey was divided into two parts: early and late first-trimester. The survey was focused on safety issue, nuchal translucency (NT) cutoff, the anatomic structures they check, and the need for practical recommendations or educational courses during the first-trimester. RESULTS: During the study period, 194 KSUOG members participated into this survey. The survey on early first-trimester scan reveal that 173 (89.2%) of respondents had used pulsed-wave Doppler or color Doppler imaging to monitor fetal heart beat. For the late first-trimester scan, 145 (74.7%) of respondents was found to check for fetal anatomical assessments during their NT screening performance; however, the clinical practice patterns were considerably varied among participants. More than half of the respondents used the criterion of NT ≥3.0 mm to define increased NT. Approximately 80% of respondents stated that the screening ultrasonography of fetal structures in the first-trimester was necessary. Furthermore, 187 (96.4%) of respondents were in favor of a recommendation for first-trimester ultrasonography in Korea. CONCLUSION: This is the first survey of the current clinical practice of first-trimester ultrasonography in Korea. Our survey findings highlight the need for the practical recommendation or educational course for first-trimester ultrasonography.